The Fulbright Impact Study in the Academic Fields of Arts, Social Sciences and Natural Sciences in Hungary Between 1984 and 2011 - Kővári , Csilla (AMERICANA E-journal of American Studies in Hungary, 2022)
The article analyzes with a quantitative survey the effects of the Fulbright mobility on the competences of the participants (researchers, lecturers, students, high school teachers and other participants of the Program) and the internationalization of Higher Education Institutions in Hungary in the period of 1984-2011 by discussing the effects of Fulbright mobility on individual skills and examining the impact of the Fulbright Program on the internationalization of Higher Education Institutions in Hungary.